Analisis Prosedur Pemberian Pembiayaan Multiguna Pada Pt. Bank Sumut Kantor Cabang Pembantu Syariah Karya - Sari, Suspita; Jannah, Nurul (Regress: Journal of Economics & Management, 2022)
This research is motivated by the increasing number of customers who want to apply for Multipurpose financing in order to meet their daily needs such as motorcycles and others, in an effort to improve the standard of living of prospective customers. The purpose of this study is how the procedures established in the provision of Multipurpose Financing implemented by PT. Bank Sumut Sharia Karya Sub-Branch Office and how to overcome obstacles during the process of providing Multipurpose Financing. The research method used is qualitative with a descriptive approach. Sources and types of data used in this study are primary data obtained from the field by observation or interview methods. Researchers get additional data through various sources, ranging from books, online journals, articles, news, and previous research as supporting data and complementary data. The results of the study explain that at PT. Bank Sumut Syariah Karya Sub-Branch Office has implemented the procedure for providing Multipurpose financing correctly and optimally, starting from the application process to the final stage. In overcoming obstacles, the bank has checked customer files carefully, then during the financing analysis process and making the contract, the bank provides opportunities for interns to participate in helping the process to be well organized.